2008
DOI: 10.1111/j.1365-3091.2008.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

Tufas and travertines of the Mediterranean region: a testing ground for freshwater carbonate concepts and developments

Abstract: Actively forming travertine and tufa sites are widespread in temperate and warm climates, such as the Mediterranean region, but also develop in other climatic regimes from the Arctic to equatorial latitudes. The terms travertine and tufa are sometimes applied indiscriminately today; however, each has a specific definition. Most studied deposits are active or of Quaternary (especially Holocene) age. There are fewer Tertiary and even less late Mesozoic examples on record. In part, this is because of a recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
169
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(181 citation statements)
references
References 86 publications
(153 reference statements)
6
169
0
6
Order By: Relevance
“…), dissolution Lopez et al (2017), Westaway (1993), Pentecost et al (1997), Kele et al (2011), De Filippis et al (2012, Özkul et al (2013), Van Noten et al (2013), Lebatard et al (2014), Claes et al (2015Claes et al ( , 2017aClaes et al ( , 2017b Sorey and Colvard (1997), Fouke et al (2000Fouke et al ( , 2003, Kharaka et al (2000), Chafetz and Guidry (2003), Kandianis et al (2008), Veysey et al (2008) Cipriani et al (1977), Barazzuoli et al (1988), Guo and Riding (1992, Pentecost (1995), Minissale et al (2002), Brogi et al (2007), Brogi and Capezzuoli (2008), Pedley (2009), Gandin and Capezzuoli (2014) Arp et al (2001Arp et al ( , 2010, Shiraishi et al (2008aShiraishi et al ( , 2008b, Brinkmann et al (2015) (continued on next page) et al, 2012; Nielsen et al, 2014). Lab and field studies report ACC phases found in close association with crystalline CaCO 3 (Jones and Peng, 2012a;Pedley, 2014) and/or organisms (cyanobacteria) or organic substances (Couradeau et al, 2012;Benzerara et al, 2014;Martignier et al, 2017).…”
Section: Tablementioning
confidence: 99%
“…), dissolution Lopez et al (2017), Westaway (1993), Pentecost et al (1997), Kele et al (2011), De Filippis et al (2012, Özkul et al (2013), Van Noten et al (2013), Lebatard et al (2014), Claes et al (2015Claes et al ( , 2017aClaes et al ( , 2017b Sorey and Colvard (1997), Fouke et al (2000Fouke et al ( , 2003, Kharaka et al (2000), Chafetz and Guidry (2003), Kandianis et al (2008), Veysey et al (2008) Cipriani et al (1977), Barazzuoli et al (1988), Guo and Riding (1992, Pentecost (1995), Minissale et al (2002), Brogi et al (2007), Brogi and Capezzuoli (2008), Pedley (2009), Gandin and Capezzuoli (2014) Arp et al (2001Arp et al ( , 2010, Shiraishi et al (2008aShiraishi et al ( , 2008b, Brinkmann et al (2015) (continued on next page) et al, 2012; Nielsen et al, 2014). Lab and field studies report ACC phases found in close association with crystalline CaCO 3 (Jones and Peng, 2012a;Pedley, 2014) and/or organisms (cyanobacteria) or organic substances (Couradeau et al, 2012;Benzerara et al, 2014;Martignier et al, 2017).…”
Section: Tablementioning
confidence: 99%
“…Often, a distinction has been made between cool water 'tufa' and warm or hot water 'travertine' deposits (Ford and Pedley, 1996;Pedley, 2009). Such classification, however, proves difficult when mapping ancient travertine in the field (Brasier, 2011;Capezzuoli et al, 2014;Cantonati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The term tufa is used to de note such de pos its if they com prise macro-or microphyte moulds or im prints (Pedley, 2009). How ever, some au thors ex tend the mean ing of the term "trav er tine" to such depos its (see Gandin and Cappezuoli, 2008 as well as Jones and Renaut, 2010, for ter mi no log i cal dis cus sion).…”
Section: Introductionmentioning
confidence: 99%